2023
DOI: 10.4274/mirt.galenos.2022.68094
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of CT-based Attenuation-correction in Myocardial Perfusion SPECT Imaging

Abstract: Objectives: We aimed to investigate and compare the role of computed tomography (CT)-based attenuation-corrected images (AC) with non-attenuation-corrected images (NAC) obtained by single-photon emission computed tomography/computed tomography (SPECT/CT) myocardial perfusion imaging (MPI). Methods: The data of 124 patients who were applied one-day stress-rest Tc-99m sestamibi SPECT/CT MPI and who had coronary angiography (CAG) results within ±3 months were retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…In clinical practice, it has been observed that obesity or breast tissue in female patients can cause sparse or defective perfusion in the inferior or anterior wall of MPI, leading to false positives. This is primarily attributed to the attenuation of γ photons as they pass through human tissues, with male patients experiencing attenuation primarily at the diaphragm, and female patients, especially those with enlarged and dense mammary glands, experiencing attenuation in the mammary gland 11,12 . However, with the signi cant advantages of CTAC, which provides precise anatomical positioning information and accurate attenuation correction data for MPI, we can obtain higher-quality MPI tomographic images.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, it has been observed that obesity or breast tissue in female patients can cause sparse or defective perfusion in the inferior or anterior wall of MPI, leading to false positives. This is primarily attributed to the attenuation of γ photons as they pass through human tissues, with male patients experiencing attenuation primarily at the diaphragm, and female patients, especially those with enlarged and dense mammary glands, experiencing attenuation in the mammary gland 11,12 . However, with the signi cant advantages of CTAC, which provides precise anatomical positioning information and accurate attenuation correction data for MPI, we can obtain higher-quality MPI tomographic images.…”
Section: Discussionmentioning
confidence: 99%